Monetary Policy, Credit Conditions, and Dollarization under Nonlinear Inflation Dynamics: Evidence from Laos using NARDL - KHOUTPHILAVANH, Lamtiane; Fan, Zuojun (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The evidence on the transmission of monetary policy is still limited, particularly in terms of nonlinear effects, despite the high dollarization and structural weaknesses in the financial system of Lao PDR. This study fills this gap by examining whether policy rate changes have asymmetric impacts on inflation in this dollarized economy. We employ a Nonlinear Autoregressive Distributed Lag (NARDL) model to investigate the impact of policy rate fluctuations on inflation from 1992 to 2024. Credit conditions, aggregate demand, and dollarization are all considered. Three primary discoveries are identified. Initially, long-term inflation is influenced by structural factors namely, dollarization, aggregate demand, and credit conditions rather than interest rate channels. Secondly, policy rate increases have a modest positive effect (0.0308, p < 0.10), whereas rate reductions have no significant impact. Third, Wald tests verify the long-term asymmetry in monetary transmission. These findings suggest that price stability cannot be achieved solely through interest rate adjustments in highly dollarized economies such as Laos. An expanded framework that encompasses de-dollarization, credit regulation, exchange rate stabilization, and liquidity management is required.